Rethinking political Islam in Malaysia: a case study of Parti Amanah Negara (AMANAH) - Malik, Maszlee (International Institute of Advanced Islamic Studies (IAIS), 2017)
A group of sidelined and outcast progressive leaders and activists of the Islamic party of Malaysia, or the ‘Parti Islam SeMalaysia’ (PAS) left the party after its 2015 Muktamar (Annual General Assembly) to form Parti Amanah Negara (AMANAH) along with other like-minded Islamic organizations’ members. The establishment of this new party was linked to the effort to save the moderate Islamic political thought that was once embraced by PAS. They claimed that the new leadership of PAS elected in the 2015 Muktamar is alleged to have a more conservative position. The establishment of this new party was claimed by its founders as their effort to save the moderate Islamic political thought that was once embraced by PAS. According to AMANAH founders, the party is established to bring Islamic political activism into a new paradigm, with the hope to shape the future discourse of Muslims in Malaysia which is more inclusive, moderate, democratic and progressive. This article is an attempt to understand the party’s ideology, which they claim as a ‘new discourse’ of political Islam, and to evaluate the level of adherence and consistency of AMANAH members towards this ideology through a qualitative study conducted on 100 party members from different levels.